2015
DOI: 10.1134/s1995082915020121
|View full text |Cite
|
Sign up to set email alerts
|

Thermoindicator properties of phytoplankton species (by the example of waterbodies of the Southern Urals)

Abstract: Abstract⎯Thermoindicator properties of phytoplankton in waterbodies of the Southern Urals are deter mined, and a list of indicator species is compiled. The groups of stenothermal and eurythermal species, as well as those of cryobiontic, cryophilic, thermophilic, and thermobiontic organisms, have been distinguished. A comparison of the thermal indicators with the known ones is made. The list of thermal indicator species makes it possible to analyze changes in waterbodies under the impact of global warming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The summer warming decreased its cell density because the high temperature exceeded its growth temperature range. The results presented here and the field observations of other authors also suggest that the Fragilaria genus is a eurythermal genus capable of surviving over a wide range of temperatures [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 80%
“…The summer warming decreased its cell density because the high temperature exceeded its growth temperature range. The results presented here and the field observations of other authors also suggest that the Fragilaria genus is a eurythermal genus capable of surviving over a wide range of temperatures [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 80%
“…For example, Shear et al (1976) showed that in Rice Lake (USA), A. granulata (as Melosira granulata) only appeared in summer (~8%) while A. ambigua (as Melosira ambigua) was dominant for the rest of the year (representing ~80%). Similarly, Snitko et al (2015) inferred from a large dataset of plankton samples collected in shallow lakes in the mountain-forest zone of the southern Urals (Russia) that A. ambigua is a stenothermal cryophilous species while A. granulata is a eurythermal thermobiont. All these results indicate that A. ambigua is able to grow in lower water temperatures, compared to A. granulata-related taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Change in the strength and duration of water-column mixing. The mass vegetation of Aulacoseira species in water bodies of the Southern Urals occurs in cold water in late autumn (Snitko et al, 2015). Aulacoseira species favouring strongly mixed water column were alternated by assemblages with Puncticulata radiosa preferring weakly mixing water column (Barinova et al, 2006).…”
Section: Climate Warming and Aridization (~10300-9000 Cal Bp)mentioning
confidence: 99%